2015
DOI: 10.3168/jds.2015-9386
|View full text |Cite
|
Sign up to set email alerts
|

Cultural lag: A new challenge for mastitis control on dairy farms in the United States

Abstract: Recent changes in the US dairy industry include increases in herd size and the proportion of milk that is produced by large herds. These changes have been accompanied by an increased reliance on hired employees and an increasing role of immigrant labor to perform critical tasks such as milking cows. Thus, there is a growing need for training and education programs for dairy employees because many employees lack previous dairy experience and employee turnover rates are problematic on many farms. Although extens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 8 publications
(15 reference statements)
0
32
0
1
Order By: Relevance
“…In order to maximize engagement, it is important to acknowledge that workers may not view safety as their number one priority and build OSH content into trainings on other topics that workers view as higher priorities (which can be identified through formative research) (44). Workers should be consulted regarding the ideal duration and scheduling of OSH trainings (75, 89). A high level of engagement can also be promoted by collaborating with community organizations that already have a well-established relationship with the immigrant, Latino/a community [e.g., Ref.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to maximize engagement, it is important to acknowledge that workers may not view safety as their number one priority and build OSH content into trainings on other topics that workers view as higher priorities (which can be identified through formative research) (44). Workers should be consulted regarding the ideal duration and scheduling of OSH trainings (75, 89). A high level of engagement can also be promoted by collaborating with community organizations that already have a well-established relationship with the immigrant, Latino/a community [e.g., Ref.…”
Section: Resultsmentioning
confidence: 99%
“…Another major difficulty related to promoting OSH among immigrant, Latino/a dairy workers lies in the considerable communication barriers between workers and non-Latino/a dairy owners and managers (89). In addition to OSH training, ESL and SSL classes should be provided to improve communication and comprehension of OSH materials (109).…”
Section: Discussionmentioning
confidence: 99%
“…From this, it appears that training is key to an organization's productivity. Erskine et al (2015) piloted a survey of management culture on dairy farms with results that suggested extension needed to build capacity for on-farm training and education of employees to stay engaged with dairy operations. Their work also highlighted the important role that veterinarian-initiated education can have on employee attitudes toward their jobs and the economic value perceived by owners.…”
Section: Discussionmentioning
confidence: 99%
“…This knowledge is not only important to develop understanding of the need for consistency when following a protocol, but may also help improve understanding and establishment of common herd health-related objectives within the farm, reducing potential barriers introduced by miscommunication. Because employees both desire and need to understand the "why" of what they do is important (Erskine et al, 2015), training programs, particularly for new employees responsible for animal treatments, need to include an in-depth introduction to the diseases, their causes, and why certain treatments are appropriate. These programs should be provided by someone able to answer employees' questions on disease and appropriate drug use (i.e., a veterinarian).…”
Section: Discussionmentioning
confidence: 99%
“…Along the way, farmers can compare their own farm performance, share experiences, and learn from examples (Campbell et al, 2006;Scottish Monitor Farms Programme, 2014). Similarly, "demonstration projects" can be used to assess the outcomes of corresponding methods or processes applied to several farms (Piepers et al, 2011;Erskine et al, 2015) Numerous variations of these 3 approaches exist, but they are generally underpinned by participatory learning or participatory action research.…”
Section: Toolsmentioning
confidence: 99%